William Shakespear : Hamlet - Shahid Hussain, Syed (Lahore Kitab Mahal)
The first book in the Snopes trilogy, The Hamlet tells the story of Ab Snopes's arrival in the rural community of Frenchman's Bend; his son Flem's rise to power; and his family's transition from outcasts to central, if dangerous, players in the life of the town. With a memorable cast of characters that appear in many of William Faulkner's other works, The Hamlet is a commentary on post-war conditions in the American
Keywords: Tragedy -- Delay -- Hamlet's Madness